Shaping Streetscapes within the Complexities of Urban Informalities in the Cape Flats - Mbambo, Zizipho (School of Architecture, Planning and Geomatics, 2024)
This study focuses on investigating the role of Landscape Architecture in shaping the Khayelitsha's Mew Way Road. Khayelitsha is located on the outskirts of Cape Town, South Africa. Khayelitsha is characterized by a mix of formal and informal housing, with By recognizing the importance of inclusive design, this research explores how Landscape Architecture can contribute to creating functional and vibrant streetscapes that effectively respond to the needs and aspirations of the local community. Utilizing a qualitative research approach, including in-depth interviews, site observations, and design analysis, this study aims to identify strategies for designing streetscapes that better accommodate and enhance informal social and economic activities in Khayelitsha. Finally, the streetscape design strategies are tested in a design intervention that aims to accommodate informal social and economic activities and make use of place-making interventions to support livelihoods and well-being. By building on existing energies in the informal settlement / embracing informal activities, improving services, and creand shaded areas for trading. KEY WORDS: Landscape Architecture, urban informality, streetscape design, place making principles, infrastructural intervention, cultural activities, Cape Flats, inclusivity,informal social and economic activities.